Intimate Partner Violence in Fiji: How the Perpetrator Is “Rewarded” for Perceived Victim Suffering - Johnson, James (Violence against women, 2023)
Although intimate partner violence is rampant in Fiji, limited research has investigated the perception of appropriate legal sanctions for the perpetrators. We explored whether victim characteristics and perceived victim suffering would independently or jointly influence perpetrator-directed legal sanctions. Undergraduates read an IPV passage with the victim portrayed as a sexual norm violator, a career-focused mother, or a control victim. At high levels of perceived victim suffering, participants “rewarded” the perpetrator by reporting less punitive reactions and reduced perceived culpability in the norm violating victim condition. No differences emerged at low levels of perceived suffering. Implications for the Metanorm Perspective are discussed.